2009
DOI: 10.1007/s10895-009-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective Critical Micellar Concentration of a Zwitterionic Detergent: A Fluorimetric Study on n-Dodecyl Phosphocholine

Abstract: We have investigated the effect of ionic strength on the aggregation behavior of n-dodecyl phosphocholine. On the basis of the classical Corrin-Harkins relation, the critical micellar concentration of this detergent decreases with a biphasic trend on lithium chloride addition. It is nearly constant below 150 mM salt, with a mean value of 0.91 mM, whereas it undergoes a dramatic 80-fold decrease in 7 M LiCl. Such a drop in the critical micellar concentration could be explained by the effect of salting out and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
2
34
0
1
Order By: Relevance
“…S1). Therefore, our simulation data support the existence of detergent-mediated protein aggregation in the presence of salt, although we note that chloride ions (used in these simulations) differ from phosphate ions (used by Hwang et al (Hwang et al, 2002) for NMR), and salt concentrations up to 7 M affect the critical micelle concentration of DPC (Palladino et al, 2010).…”
Section: Aggregated Statessupporting
confidence: 69%
“…S1). Therefore, our simulation data support the existence of detergent-mediated protein aggregation in the presence of salt, although we note that chloride ions (used in these simulations) differ from phosphate ions (used by Hwang et al (Hwang et al, 2002) for NMR), and salt concentrations up to 7 M affect the critical micelle concentration of DPC (Palladino et al, 2010).…”
Section: Aggregated Statessupporting
confidence: 69%
“…Titration with DPC Suggests Surface Interactions-Addition of aliquots from a concentrated solution of DPC into a 1 mM 15 N CHR peptide at pH 7.6 was carried out by making sure that the first addition yielded a concentration of DPC (14 mM) in the sample that is well above the critical micelle concentration (1.1 mM) of DPC in pure water (29,30). Measurement of the critical micelle concentration of DPC using 31 P NMR showed that the chemical shift of the headgroup phosphorous reached the value associated with a micellar environment at 3-4 mM (30).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of zwitterionic DPC, this effect is less pronounced because of the overall neutral charge of the surfactant. Therefore, it is proposed that the drop in the cmc of DPC might be due to salting out and the implication of phosphocholine headgroups in organization of the surrounding water molecules [42]. It is worth noting that for the 9:1 DPC/SDS system, the change in cmc observed upon transfer from the unbuffered to buffered solution is negligible (taking into account cmc1 in PBS).…”
Section: Mixed Micelles In Unbuffered Solutionmentioning
confidence: 99%